Quantitative MRI analysis of brain volume changes due to controlled cortical impact. - O'MARA, SHANE; GOBBO, OLIVIERO (My University, 2010)
More than 85% of reported brain traumas are classified clinically as "mild" using the Glasgow Coma Scale (GCS); qualitative MRI findings are scarce and provide little correspondence to clinical symptoms. Our goal, therefore, was to establish in vivo sequelae of traumatic brain injury (TBI) following lower and higher levels of impact to the frontal lobe using quantitative MRI analysis and a mechanical model of penetrating impact injury. To investigate time-based morphological and physiological changes of living tissue requires a surrogate for the human central nervous system. The present model for TBI was a systematically varied and controlled cortical impact on deeply-anaesthetized Sprague-Dawley rats, that was designed to mimic different injury severities. Whole-brain MRI scans were performed on each rat prior to either a lower- or a higher-level of impact, and then at hourly intervals for 5 h post-impact. Both brain volume and specific anatomical structures were segmented from MR images for inter-subject comparisons post-registration. Animals subjected to lower and higher impact levels exhibited elevated intracranial pressure (ICP) in the low compensatory reserve (i.e., nearly exhausted), and terminal disturbance (i.e., exhausted) ranges, respectively. There was a statistically significant drop in cerebrospinal fluid (CSF) of 35% in the lower impacts, and 65% in the higher impacts, at 5 h compared to sham controls. There was a corresponding increase in corpus callosum volume starting at 1 h, of 60-110% and 30-40% following the lower- and higher-impact levels, respectively. A statistically significant change in the abnormal tissue from 2 h to 5 h was observed for both impact levels, with greater significance for higher impacts. Furthermore, a statistically significant difference between the lower impacts and the sham controls occurred at 3 h. These results are statistically substantiated by a fluctuation in the physical size of the corpus callosum, a decrease in the volume of CSF, and elevated levels of atrophy in the cerebral cortex.
PUBLISHED
Keywords: Neuroscience; brain trauma; Neuroscience